Orthographic Abbreviation in Babylonian and Assyrian of the Second and First Millennia BC - Worthington, Martin ca. 20./21. Jh. (Henoch, 2020)
Lipographies (accidental omissions of signs) are, it has several times been observed, legion in Babylonian and Assyrian writings. But signs could also be omitted intentionally, to abbreviate the spelling of words. This latter phenomenon has again been remarked on (usually in ad hoc comments by editors), but never subjected to wide-ranging scrutiny and systematisation. Such is the aim of this paper. Drawing on examples from multiple periods and textual typologies (‘genres’), we will distinguish abbreviation at the level of spelling from other forms of abbreviation, and enquire after the rationales and practices attaching to abbreviations in spelling. The resulting picture, which both challenges and refines previous statements on the subject, is a first attempt at systematising a phenomenon which offers great potential for the detailed study of individual text corpora. As studies of abbreviation in the Hebrew Bible demonstrate, there may well ultimately be significant implications for textual criticism.